President Abdurrahman Wahid’s Efforts to Consolidate the Democratic Transition from the Soeharto Authoritarian Regime - Saefur Rochmat (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
Abdurrahman Wahid was appointed by MPR (the Indonesian People’s Representative Assembly) as the President of the Republic of Indonesia because of his idea of democracy, convincing the prevailing two opposing groups, namely the nationalist groups and Islamist groups (it is well- known as Poros Tengah/ the Central Axis). Indeed, he was able to adapt democracy to the Islamic tradition by employing the fiqh-plus paradigm to the relationship between Islam and the state. He made uses of the presidential office to consolidate the democratic transition such as by supporting civil society, establishing civil supremacy and establishing law enforcement. From beginning it was not easy for him to socialise his fiqh-plus paradigm to other Islamic groups. Moreover, Central Axis, the determining force contributing to the win of Wahid’s presidential election, felt upset with Wahid’s policies which did not align with their interests. The nationalist groups were also anxious about occupying the presidential office for themself. Last but not the least, the military also agreed with the idea of impeachment of President Wahid in order to save their political interests.DOI: 10.15408/insaniyat.v1i2.5473